1994
DOI: 10.1104/pp.104.2.747
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dehydroproline Inhibits Cell Wall Assembly and Cell Division in Tobacco Protoplasts

Abstract: We investigated the function of cell wall hydroxyproline-rich glycoproteins by observing the effects of a selective inhibitor of prolyl hydroxylase, 3,4-dehydro-i-proline (Dhp), on wall regeneration by Nicofiana fabacum mesophyll cell protoplasts. Protoplasts treated with micromolar concentrations of Dhp do not develop osmotic stability and do not initiate mitosis. l h e architecture of regenerated cell walls was examined using deep-etch, freezefracture electron microscopy of rapidly frozen tobacco cells. Untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 20 publications
1
52
0
2
Order By: Relevance
“…recognition and binding) of BLC by Rhizobium sp.YAS34GFP was strongly modified upon DHP treatment. DHP is known to inhibit Pro-hydroxylation and to specifically induce the synthesis and the secretion of structurally abnormal Hyp-rich glycoproteins, including AGPs (Cooper and Varner, 1983;Cooper et al, 1994;Gateau and Driouich, unpublished data). The effect of DHP on the association of the rhizobium to BLC is probably due to alterations of the structure of AGPs or other Hyp-containing wall proteins such as extensins and repetitive-Pro-rich protein.…”
Section: For This Reason and To Distinguish Them From The Classical Bmentioning
confidence: 99%
See 2 more Smart Citations
“…recognition and binding) of BLC by Rhizobium sp.YAS34GFP was strongly modified upon DHP treatment. DHP is known to inhibit Pro-hydroxylation and to specifically induce the synthesis and the secretion of structurally abnormal Hyp-rich glycoproteins, including AGPs (Cooper and Varner, 1983;Cooper et al, 1994;Gateau and Driouich, unpublished data). The effect of DHP on the association of the rhizobium to BLC is probably due to alterations of the structure of AGPs or other Hyp-containing wall proteins such as extensins and repetitive-Pro-rich protein.…”
Section: For This Reason and To Distinguish Them From The Classical Bmentioning
confidence: 99%
“…To gain information on the role of BLC and AGPs in the recognition/adhesion mechanism between root cells and microorganisms, we examined the effects of b-GlcY reagent known for its ability to bind and precipitate AGPs (Fincher et al, 1983), and DHP, a reagent that can inhibit the O-glycosylation of cell wall proteoglycans, including AGPs (Cooper and Varner, 1983;Cooper et al, 1994;Gateau and Driouich, unpublished data). Alpha-mannosyl Yariv reagent (a-ManY), which is a nonreactive analog of b-GlcY, was used as a control.…”
Section: Role Of Agps In the Interaction Between Root Blc And Microormentioning
confidence: 99%
See 1 more Smart Citation
“…3,4-DHP is an inhibitor of Hyp biosynthesis that is necessary for extensin glycosylation (Cooper et al, 1994). Root apices were first agitated to remove loosely attached border cells and then incubated in growth medium supplemented with 200 mM 3,4-DHP (Fig.…”
Section: The Role Of Extensin Glycosylation and Hg Deesterification Imentioning
confidence: 99%
“…3,4-DHP treatment of soybean cells was also shown to induce disappearance of the major PRPs from the cell wall of cultured cells (Schmidt et al, 1991), and 3,4-DHP-treated protoplasts do not develop osmotic stability and do initiate mitosis. 3,4-DHP-treated carrot root cells continue to synthesize and secrete structurally abnormal extensin HRGPs that might be expected to function abnormally (Cooper et al, 1994). Others studies showed that treatment of onion root cells by 3, 4-DHP resulted on a 56% decrease in hydroxyproline content (Tullio et al, 1999).…”
Section: Introductionmentioning
confidence: 99%